2021
DOI: 10.3389/fphys.2021.666941
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Recruitment Maneuver on Lung Aeration Through Imaging Analysis in Invasively Ventilated Patients: A Systematic Review

Abstract: Background: Recruitment maneuvers (RMs) have heterogeneous effects on lung aeration and have adverse side effects. We aimed to identify morphological, anatomical, and functional imaging characteristics that might be used to predict the RMs on lung aeration in invasively ventilated patients.Methods: We performed a systemic review. Studies included invasively ventilated patients who received an RM and in whom re-aeration was examined with chest computed tomography (CT), electrical impedance tomography (EIT), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…The observation of A-lines in previously collapsed regions could be a potential marker of lung overdistension if maneuvers are not stopped at that point. The benefit of RMs needs to be balanced between reaeration and overdistention [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observation of A-lines in previously collapsed regions could be a potential marker of lung overdistension if maneuvers are not stopped at that point. The benefit of RMs needs to be balanced between reaeration and overdistention [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between PEEP responders and nonresponders is important to avoid PEEP-induced lung strain. Classically, responders are patients who improve oxygenation, compliance, driving pressure, or dorsal aeration after an RM or stepwise increments in PEEP (28, 39). Using EIT, Wolf et al (40) observed that, after applying a stepwise RM, improvements in dorsal collapse preceded physiologic recruitment (Pa co 2 + Pa o 2 > 400 mm Hg).…”
Section: Clinical Applications Of Electrical Impedance Tomography − P...mentioning
confidence: 99%
“…Diagnosing, monitoring and resolving atelectasis while preventing overdistention is one of the main challenges in the mechanical ventilation. Computed tomography (CT) is the golden standard for the assessment of aeration and potential for recruitment in ARDS [ 16 , 17 ], but lacks the practicality of bedside monitoring. Especially when resources are constrained due to an epidemic, bedside monitoring might serve as a viable or even essential alternative.…”
Section: Volumes and Aerationmentioning
confidence: 99%